Implementations of MGNREGS in Punjab: Major Problems and Suggestions - Kaur, Teavaspreet (Gyan Management Journal, 2016)
Mahatma Gandhi National Rural Employment Guarantee Scheme had a very positive impact on the poor people of the country to enhancing the quality of life in rural areas. This paper aims to highlight the utilization of funds and the problems associated with implementation ofMG-NREGS in all district of Punjab State. The analysis revealed that lack of proper planning and implementation of scheme by the g
Keywords: Unemployment; Social Schemes; MGNREGS; Works; Planning